(untitled) (Marketing Journal, 2025)
The article explores the integration of artificial intelligence and digital technologies in banking marketing. The study highlights the role of machine learning, deep learning, RPA, and cloud technologies in improving banking services. Based on a conceptua l model, it demonstrates how data processing, customer segmentation, service personalization, and process automation enhance marketing efficiency. The findings confirm that these technologies strengthen banksʼ competitiveness, accelerate innovation, and su pport long -term customer relationships. 288